Analisis sektor unggulan di Kabupaten Kerinci - Gufron Sulman; Syamsurijal Tan; Zamzami Zamzami (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2017)
This study aims to analyze the leading sectors in the economy in Kerinci Regency. The data used are secondary in the period 2011-2016, which was sourced from the Central Bureau of Statistics of Jambi Province and Kerinci Regency. The analysis tool uses Location Quotient analysis and Shift Share analysis. The results of the study found that the leading sectors in Kerinci Regency were the agriculture, forestry and fisheries sector, the water supply sector, waste management and recycling, the real estate sector, the health services and social activities sector